2016
DOI: 10.1007/s10909-016-1491-2
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Energy Calibration of X-ray TESs with 0.04 eV Uncertainty at 6.4 keV in a Hadron-Beam Environment

Abstract: A performance evaluation of superconducting transition-edge sensors (TESs) in the environment of a pion beam line at a particle accelerator is presented. Averaged across the 209 functioning sensors in the array, the achieved energy resolution is 5.2 eV FWHM at Co K α (6.9 keV) when the pion beam is off and 7.3 eV at a beam rate of 1.45 MHz. Absolute energy uncertainty of ±0.04 eV is demonstrated for Fe K α (6.4 keV) with in-situ energy calibration obtained from other nearby known x-ray lines. To achieve this s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 12 publications
(17 reference statements)
3
16
0
1
Order By: Relevance
“…placed atop of the TES, tests have shown that this material affects the detector response causing an undesirable tail on the low energy side of a monochromatic energy peak. The same behavior concerning bismuth absorbers was found in different TES microcalorimeters [20]. Furthermore, by replacing the bismuth with gold and maintaining the same design, the transition shape showed suppression of the T c due to proximity effects of the superconductor beneath the gold layer [21]: this is reflected in an undesirable kink in the transition shape which in turn causes strong non-linearity in the detector response.…”
Section: Detector Designsupporting
confidence: 53%
“…placed atop of the TES, tests have shown that this material affects the detector response causing an undesirable tail on the low energy side of a monochromatic energy peak. The same behavior concerning bismuth absorbers was found in different TES microcalorimeters [20]. Furthermore, by replacing the bismuth with gold and maintaining the same design, the transition shape showed suppression of the T c due to proximity effects of the superconductor beneath the gold layer [21]: this is reflected in an undesirable kink in the transition shape which in turn causes strong non-linearity in the detector response.…”
Section: Detector Designsupporting
confidence: 53%
“…Typically, one or multiple strong lines in the calibration data are measured at multiple times during an ADR cycle to generate the data necessary for drift correction, but strong lines in the measured EBIT data could also be used for this purpose if they exist for a given measurement. This approach to drift correction has previously been used to achieve on order 10 −5 fractional line position accuracy 80,81 . In addition to the drift in pulse height throughout an ADR cy-cle, there is also a small amount of pulse height variation between different ADR cycles (detectors typically show ∼ 10 −4 − 10 −3 cycle-to-cycle variation in fractional pulse height when measured at the same time after the start of an ADR cycle).…”
Section: Data Reductionmentioning
confidence: 99%
“…One of the keys in this highprecision measurement is the absolute energy calibration for every single readout channel. We use the X-ray generators and secondary target metals of chromium, cobalt, and copper based on the result of a test experiment [6,7]. Details of the experimental setup are described in reference [8].…”
Section: Kaonic Helium 3d → 2p With Tes (J-parc E62)mentioning
confidence: 99%